Dasatinib treatment of chronic-phase chronic myeloid leukemia: analysis of responses according to preexisting BCR-ABL mutations - Müller, Martin C.; Cortes, Jorge E.; Kim, Dong-Wook; Druker, Brian J.; Erben, Philipp; Pasquini, Ricardo; Branford, Susan; Hughes, Timothy P.; Radich, Jerald P.; Ploughman, Lynn; Mukhopadhyay, Jaydip; Hochhaus, Andreas (Blood, 2009)
Dasatinib is a BCR-ABL inhibitor with 325-fold higher potency than imatinib against unmutated BCR-ABL in vitro. Imatinib failure is commonly caused by BCR-ABL mutations. Here, dasatinib efficacy was analyzed in patients recruited to phase 2/3 trials with chronic-phase chronic myeloid leukemia with or without BCR-ABL mutations after prior imatinib. Among 1043 patients, 39% had a preexisting BCR-ABL mutation, including 48% of 805 patients with imatinib resistance or suboptimal response. Sixty-threedifferent BCR-ABL mutations affecting 49 amino acids were detected at baseline, with G250, M351, M244, and F359 most frequently affected. After 2 years of follow-up, dasatinib treatment of imatinib-resistant patients with or without a mutation resulted in notable response rates (complete cytogenetic response: 43% vs 47%) and durable progression-free survival (70% vs 80%). High response rates were achieved with different mutations except T315I, including highly imatinib-resistant mutations in the P-loop region. Impaired responses were observed with some mutations with a dasatinib median inhibitory concentration (IC50) greater than 3nM; among patients with mutations with lower or unknown IC50, efficacy was comparable with those with no mutation. Overall, dasatinib has durable efficacy in patients with or without BCR-ABL mutations. All trials were registered at http://www.clinicaltrials.gov as NCT00123474, NCT00101660, and NCT00103844.